2020
DOI: 10.3390/land9090316
|View full text |Cite
|
Sign up to set email alerts
|

Abandonment and Recultivation of Agricultural Lands in Slovakia—Patterns and Determinants from the Past to the Future

Abstract: Central and Eastern Europe has experienced fundamental land use changes since the collapse of socialism around 1990. We analyzeanalyzed the patterns and determinants of agricultural land abandonment and recultivation in Slovakia during the transition from a state-controlled economy to an open-market economy (1986 to 2000) and the subsequent accession to the European Union (2000 to 2010). We quantified agricultural land-use change based on available maps derived from 30-m multi-seasonal Landsat imagery and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 105 publications
0
34
0
Order By: Relevance
“…The significant difference in the distance to old-woods reflects the general tendency to overgrow the fields located near the forest edge and further from the village first. Pazúr et al [70] showed, for Slovakia, that those abandoned farmlands which were located further away from the forest edge were re-cultivated. Furthermore, in Russia, the transition from farmland to forest was more likely to be closer to the forest edge [63].…”
Section: Discussionmentioning
confidence: 99%
“…The significant difference in the distance to old-woods reflects the general tendency to overgrow the fields located near the forest edge and further from the village first. Pazúr et al [70] showed, for Slovakia, that those abandoned farmlands which were located further away from the forest edge were re-cultivated. Furthermore, in Russia, the transition from farmland to forest was more likely to be closer to the forest edge [63].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the HILDA model reported an increase of the abandonment rates in 1990-2000 (49.9 km 2 /year) and an extreme peak in the period 2000-2010 (290.8 km 2 /year). Increased abandonment after transition to a market-oriented economy in the period 1990-2000, followed by a decrease due to EU accession support in the period 2000-2010, was reported for Slovakia [36,41,43] and for other post-socialistic countries [24,70,71]. Because of the uncertainties related to historical land cover modelling and because of the validation results, we consider that the CHLUD dataset is a more reliable long-term data source.…”
Section: Discussionmentioning
confidence: 99%
“…However, EU accession and implementation of the Common Agriculture Policy triggered the restoration of agriculture in some areas [28,[39][40][41][42]. The agricultural land abandonment in Slovakia mostly occurred in the mountains, and it was strongly related to distance from the national capital (Bratislava), annual mean temperatures, proximity to forest edges and slope steepness [43]. Abandonment primarily affected small-scale traditional agricultural landscapes [34], and it caused adverse impacts on biodiversity and cultural heritage [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…We evaluated the models using the calculated area under the receiver operating characteristic curve (AUC) for training and validation data with a cross-validation approach, where 80% of data were used for training and 20% for validation (Elith et al, 2008;Pazúr et al, 2020;Pontius & Schneider, 2001). To parameterize the BRT models, we assessed the sensitivity of the models to the resulting AUC; namely, we tested the selection of the number of selected trees, tree complexity level (from 1 to 9), and learning rate (from 0.1 to 0.001, with a stepwise increment of 0.005).…”
Section: Revealing the Spatial Determinants Of Disturbance Eventsmentioning
confidence: 99%